Anugerah Kekudusan Dalam Surat Ibrani 12 : 28 : Inspirasi Untuk Iman Kristen - Ardianto Dua Asa; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The gift of holiness manifested in Hebrews 12:28 is the essence of the inspiration that enriches and guides the Christian faith. This message teaches us about the urgency to live with deep respect for a holy God, not only in formal worship rituals, but also in everyday aspects. It encourages us to raise moral standards, pursue holiness, and live according to God's will. More than that, the gift of holiness reminds us of the power inherent in devotion to a holy God. When we realize that we serve a God of absolute power and unshakable holiness, we gain the confidence and perseverance necessary to face the trials and challenges of life. our life's journey It is a much-needed source of inspiration in a world that is often full of trials and uncertainty